Epoxidized natural rubber 50 FBG sensor for pressure applications
ENR50 Polymer coated Fiber Bragg Grating sensor is almost a perfect choice for satisfying requirement characteristic of pressure sensor. The conventional pressure transducers are not too precise in measurement, besides being highly exposed to electromagnetic interference, power fluctuations and has complicated cabling. FBG sensor shows that it has small size, low attenuation, quick response on time, immunity to electromagnetic interference, safety in hazardous environment, and flexible configuration. However, the nature of frangible of FBG sensor is quite dangerous without packaging and coating. Therefore, the ENR50 polymer selected in this study to be a coating as it also can enhances the sensitivity of FBG sensor. ENR50 becomes a good candidate in this research because it has lower Poisson Ratio, and Young Modulus, which means it more flexible and less stiffness. Theoretical and experimental analysis was done to investigate the performance of ENR50 as FBG’s coating. Thus, the ratio sensitivity enhanced between the theoretical and experimental result of sensitivity was calculated. Beside, the ratio differentiation sensitivity of theoretical of ENR50 polymer coated FBG with bare FBG was also calculated. The performance of ENR50 coated FBG for type of pressure applications such weight and level or depth also analyzed to investigate which type of pressure applications more compatible with this kind of sensor. Theoretical result shows that ENR50 coated FBG was enhanced the sensitivity of bare FBG about 4.146 x times higher for weight applications and 4.11 x times higher for level or depth application, and this totally proved that ENR50 polymer can enhance the sensitivity of FBG bare sensor. However, experimental result not achieves the theoretical expectation due to the some limitations in the experimental setup such as the accuracy of value pressure given based on physics calculation is not as accurate compared to pressure value from the pressure chamber.